Menjawab Pandangan Dunia Mengenai Mesias Menurut Injil Matius - Rivhan Andry Wardhani Sabuna; Suleni Suleni (Manna Rafflesia, 2022)
Understanding the term Messiah in the biblical understanding of the apostle Matthew. In response to the world's understanding of the Messiah is the figure awaited by the Jews as a powerful liberator to free from suffering under the Roman empire. The image of the Messiah is also seen by Asians as a very merciful figure. Through a descriptive analysis method to literature study, research explains the understanding of the Messiah derived from the understanding of the Jewish people, before the coming of Jesus Christ as the embodiment of the OT prophecy regarding the Messiah who was sent to come to earth as the Savior of His people. The results of this study indicate that faith in Jesus Christ is getting stronger and evangelism has a focus on declaring Jesus as the Messiah.